Shape and faceting of si nanocrystals embedded in a-si o2: A Monte Carlo study - Hadjisavvas, George C.; Remediakis, Ioannis N.; Kelires, Pantelis C. (My University, 2006)
We study the equilibrium shape and faceting of Si nanocrystals embedded in a-Si O2, using continuous-space Monte Carlo simulations supplemented by the Wulff construction method. Our aim is to explain in atomistic terms why large nanocrystals are often observed to be faceted, while smaller ones are always found to be spherical. By developing and analyzing realistic structural models, we show that faceting is indeed the equilibrium state of large nanocrystals, and that it breaks down as the size shrinks. The decomposition of interface energies into bond contributions reveals that the key factors driving the destabilization of facets are the distortions of Si-O-Si bridge bonds at the edges and apeces of the unstable facets. The transition region from a faceted to a spherical shape is in the range of 4-6 nm.
Keywords: Nanocrystals; Monte-Carlo (Monaco)